Geographic scope, product diversification, and the corporate performance of Japanese firms - Delios, Andrew; Beamish, Paul W. (Strategic Management Journal, 1999)
The study extends research on the geographic scope, product diversification, and performance relationship by exploring both the antecedents and consequences of geographic scope. In so doing, it addresses a fundamental criticism of the geographic scope–performance relationship; namely, that the observed positive relationship between geographic scope and performance is spurious because it is the possession of proprietary assets that is the foundation of superior performance, not expansion into international markets per se. We tested the research model with data on the corporate performance of 399 Japanese manufacturing firms. In the partial least squares analyses used to examine the study’s six main hypotheses, we demonstrate that geographic scope was positively associated with firm profitability, even when the competing effect of proprietary assets on firm performance was considered. Further, we find that performance was not related to the extent of product diversification, although investment levels in rent-generating, proprietary assets were related to the extent of product diversification. Copyright © 1999 John Wiley & Sons, Ltd.